ИЗ ИСТОРИИ ИЗУЧЕНИЯ РЕЛИГИОЗНЫХ ТЕРМИНОВ В ОТЕЧЕСТВЕННОЙ ТЕРМИНОЛОГИИ (Scientific journal of the Fergana State University, 2026)
This article is devoted to the study of religious terms in national terminology. It also focuses on the emergence and historical development of Uzbek lexicography and terminology. The analysis shows that during the era of atheistic skepticism, little attention was paid to the study of religious vocabulary. Due to the absence of religious freedom, suppression of religious traditions, restrictions on publishing religious literature, and misinterpretation of religious concepts and terms not only in political but also in literary works, the religious lexical layer remained largely unexplored.The article highlights the development of religious dictionaries during the period of Independence and analyzes several of them in terms of structure and content. These include the English-Uzbek Dictionary of Social and Religious Terms by D. Rakhimjonov and O. Mavlanov, the Explanatory Dictionary of Spiritual and Religious Terms by J. Omonturdiyev and A. Omonturdiyev, the Dictionary of Religious Terms and Phrases by M.E. Umarkhojaev, and the Islamic Encyclopedia, which provides commentary and explanations of widely used and still relevant religious concepts.The article concludes that studying Islamic religious vocabulary and compiling religious dictionaries that reflect contemporary social processes remain pressing issues in modern Uzbek linguistics, religious studies, and translation studies.